2009
DOI: 10.1080/10428190902866732
|View full text |Cite
|
Sign up to set email alerts
|

Clinical challenges associated with bortezomib therapy in multiple myeloma and Waldenströms Macroglobulinemia

Abstract: Rapid development of the small molecule proteasome inhibitor bortezomib has yielded important clinical benefit for patients with multiple myeloma. Early phase clinical trials suggest the agent has similar efficacy in Waldenströms Macroglobulinemia. Optimization of bortezomib-based therapy, though, requires an understanding of the various challenges associated with use of the drug. This review highlights the rationale for bortezomib therapy in patients with multiple myeloma and Waldenströms Macroglobulinemia, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…1 However, not all patients with MM respond to BTZ, and most of those who do respond ultimately relapse. 1,47 These findings have stressed the importance of understanding the mechanisms underlying BTZ resistance and the identification of agents that are effective against relapsed/refractory disease. Studies of BTZ-resistant MM cell lines have demonstrated increased secretion of IGF-1 and activation of IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, not all patients with MM respond to BTZ, and most of those who do respond ultimately relapse. 1,47 These findings have stressed the importance of understanding the mechanisms underlying BTZ resistance and the identification of agents that are effective against relapsed/refractory disease. Studies of BTZ-resistant MM cell lines have demonstrated increased secretion of IGF-1 and activation of IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
“…5 This is mediated in part through both intrinsic and acquired drug resistance, the latter of which emerges during and after bortezomib therapy. 6 Response rates in patients with previously bortezomib-sensitive disease are typically decreased on drug rechallenge [7][8][9] and may be as low as 23% among patients who had achieved at least a partial remission previously. 7 These findings indicate a need for an understanding of the molecular basis for bortezomib resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic approaches for MM are not very effective due to development of resistance to drugs such as Bortezomib 34,35 . While the mechanism of resistance development to Bortezomib is not clear, it was suggested that MM progenitor cells that are CD138 À and XBP1s À are relatively resistant to Bortezomib 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, development of resistance to Bortezomib has been a major problem in MM therapy 34,35 . Thus, it is necessary to identify novel molecular targets that are necessary for the survival of both parental and Bortezomib resistant MM cells.…”
mentioning
confidence: 99%